The ParE2–PaaA2 toxin–antitoxin complex from Escherichia coli O157 forms a heterodocecamer in solution and in the crystal - Sterckx, Yann G. J. (International Union of Crystallography, 2012)
Escherichia coli O157 paaR2-paaA2-parE2 constitutes a unique three-component toxin–antitoxin (TA) module encoding a toxin (ParE2) related to the classic parDE family but with an unrelated antitoxin called PaaA2. The complex between PaaA2 and ParE2 was purified and characterized by analytical gel filtration, dynamic light scattering and small-angle X-ray scattering. It consists of a particle with a radius of gyration of 3.95 nm and is likely to form a heterododecamer. Crystals of the ParE2–PaaA2 complex diffract to 3.8 Å resolution and belong to space group P3(1)21 or P3(2)21, with unit-cell parameters a = b = 142.9, c = 87.5 Å. The asymmetric unit is consistent with a particle of around 125 kDa, which is compatible with the solution data. Therefore, the ParE2–PaaA2 complex is the largest toxin–antitoxin complex identified to date and its quaternary arrangement is likely to be of biological significance.